2015
DOI: 10.1144/jmpaleo2015-007
|View full text |Cite
|
Sign up to set email alerts
|

Recent invasion of the foraminiferNonionella stellaCushman & Moyer, 1930 in northern European waters: evidence from the Skagerrak and its fjords

Abstract: The eastern Pacific benthic foraminifer Nonionella stella Cushman & Moyer, 1930 was recorded for the first time in the Skagerrak (North Sea) and its fjords. In this short note we evaluate its migration, considering both dispersal by propagules and ship ballast tanks. We suggest that the predominantly southward surface currents along the western European seaboard and Morocco would impede a wide-range dispersal of N. stella propagules and hypothesize transportation by ship ballast tanks as the possible vector of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Nonionella sp. T1 is suggested to be an invasive species in the region which arrived by ship ballast tanks around 1985 and rapidly expanded to the Kattegat and Öresund (Asteman and Schönfeld, 2016). According to our dated core, the species arrived in the Öresund ∼ 2000 CE (Fig.…”
Section: -2009mentioning
confidence: 84%
See 1 more Smart Citation
“…Nonionella sp. T1 is suggested to be an invasive species in the region which arrived by ship ballast tanks around 1985 and rapidly expanded to the Kattegat and Öresund (Asteman and Schönfeld, 2016). According to our dated core, the species arrived in the Öresund ∼ 2000 CE (Fig.…”
Section: -2009mentioning
confidence: 84%
“…Recently, the eastern Pacific morphospecies Nonionella stella has been presented as an invasive species in the Skagerrak-Kattegat region (Asteman and Schönfeld, 2016). However, a comparison of N. stella DNA sequences from the Santa Barbara Basin (USA) (Bernhard et al, 1997) with the Swedish western coast specimens demonstrates that they represent two closely related species but are not conspecific (Deldicq et al, 2019).…”
Section: Foraminifera Analysesmentioning
confidence: 99%
“…As endemic species were not recognised, any Recent littoral or near-shore foraminifera must have been transported to the islands. A long-range transport of propagules by ocean currents or adult individuals by transocean rafting, a medium-range displacement by ichtyochory, and the introduction of alien species by marine traffic or migratory birds have been invoked as dispersal mechanisms for benthic foraminifera (McGann et al 2000;Alve & Goldstein 2003;Riedel et al 2011;Polovodova Asteman & Schönfeld 2016;Guy-Haim et al 2017;Finger 2018). Indeed, source regions of the displaced species have to be identified first before migration routes are delineated and transport mechanisms are constrained (Lübbers & Schönfeld 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several Nonionella morphospecies, bearing a star-like extension of the chambers covering the umbilicus, are described, such as Nonionella digitata Nørvang (1945), Nonionella opima Cushman (1947) or Nonionella stella Cushman and Moyer (1930). Nonionella digitata is restricted to the Arctic region (Hayward et al, 2020), whereas N. opima is identified in the Gulf of Mexico, the Mediterranean and the Bay of Biscay (Hayward et al, 2020) and N. stella is considered a cosmopolitan species (Asteman & Schönfeld, 2016). However, a recent molecular study shows specimens identified as N. stella in the Skagerrak, NE Atlantic, forming a separate clade from N. stella identified off California (Deldicq et al, 2019), and should be named differently.…”
Section: Taxonomic Assignmentmentioning
confidence: 99%